The Lower Ordovician (upper Floian) bathyurid trilobite Aponileus Hu, with species from Utah, Texas, and Greenland - Adrain, Jonathan M.; Mcadams, Neo E. B. (Zootaxa, 2012)
The previously monotypic bathyurid trilobite Aponileus Hu, 1963, was known only from poorly preserved material of itstype species, A. latus, and was interpreted as a junior subjective synonym of Psephosthenaspis Whittington. New speciesfrom the upper Floian (Blackhillsian) Fillmore Formation of western Utah belong to Aponileus and help demonstrate thatthe genus is an entirely Lower Ordovician (upper Floian) clade phylogenetically separate from the Middle Ordovician(Dapingian) Psephosthenaspis. Species of either group have broadly similar morphology, but the species of Psephosthe-naspis which most closely resembles those of Aponileus is the youngest and most derived member, and the similarities areconvergent. Psephosthenaspis roots among a group of heavily tuberculate, mostly undescribed, upper Floian species, oneof which is briefly illustrated for comparison. The species most resembling some species of Aponileus, P. glabrior, is il-lustrated on the basis of new silicified material which extends its range from the upper Juab Formation into the base of theKanosh Formation. New Blackhillsian species are A. laikaae (Fillmore Formation; Presbynileus ibexensis Zone), A. aasei(Fillmore Formation; probably Pseudocybele paranasuta Zone), A. belkaae, A. strelkaae, and A. ugolekae (all Wah WahFormation; "Pseudocybele nasuta Zone"). Aponileus? veterokae n. sp., from high in the "Pseudocybele nasuta Zone" ofthe Wah Wah Formation, is tentatively assigned. Bolbocephalus glaber Poulsen, 1927, from the Nunatami Formation ofnorthwest Greenland, is poorly known but is also a member of Aponileus, and is similar in morphology to A. latus and A.aasei; it is revised on the basis of reillustrated type material. Phylogenetic analysis indicates that A. laikaae is the basalspecies, followed by a sister pair of A. belkaae and A. strelkaae. These are sister to a pair of subclades, the sister pair of A. ugolekae and A.? veterokae, and an effaced group lacking genal spines including A. aasei, A. latus, and A. glaber.